You get what you give: children's karmic bargaining. Issue 5 (30th June 2016) - Banerjee, Konika; Bloom, Paul
Abstract: Do children believe in karma – the notion that life events occur to punish or reward our moral behavior? In three experiments, we investigate 4–6‐year‐old children's willingness to endorse and engage in the practice of performing good acts in order to secure an unrelated future desired outcome, so‐called 'karmic bargaining'. Most children agreed that performing a morally good social behavior, but not a morally negative or morally neutral non‐social behavior, would increase the chances that future desired outcomes would occur, in both first‐party and third‐party contexts. About half of children also engaged in karmic bargaining behavior themselves. We conclude that a belief in karma may therefore reflect a broad, early‐emerging teleological bias to interpret life events in terms of agency, purpose, and design. Abstract : We examine young children's belief in karmic bargaining – the practice of doing good acts in order to secure an unrelated future desired outcome. Children endorsed a belief in karmic bargaining in both first‐person and third‐person contexts, and about half of children also engaged in karmic bargaining behavior themselves. A belief in karma may reflect a broad bias to interpret life events in terms of agency, purpose, and design.